Synthesis and characterization of silver nanoparticles using fruit extract of Momordica cymbalaria and assessment of their in vitro antimicrobial, antioxidant and cytotoxicity activities - Swamy, Mallappa Kumara; Akhtar, Mohd. Sayeed; Mohanty, Sudipta Kumar; Sinniah, Uma Rani (Elsevier, 2015)
Plant mediated synthesis of nanoparticles has been considered as green route and a reliable technique for the synthesis of nanoparticles due to its eco-friendly approach. In this study, we report a simple and eco-friendly approach for the synthesis of silver nanoparticles (AgNPs) using methanolic Momordica cymbalaria fruit extract as reducing agent. The fruit extract of M. cymbalaria exposed to AgNO3 solution showed the change in color from green to light yellow at room temperature within 1 h of incubation confirms the synthesis of AgNPs. UV–vis spectra analysis revealed that the synthesized AgNPs had a sharp surface plasmon resonance at around 450 nm, while, the X-ray Diffraction (XRD) patterns confirmed distinctive peaks indices to the crystalline planes of the face centered cubic silver. The Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) analysis results confirmed the presence of spherical shaped AgNPs by a huge disparity in the particle size distribution with an average size of 15.5 nm. The synthesized AgNPs showed strong antibacterial activity against all the tested multidrug resistant human pathogenic bacterial strains and also exhibited highest free radical scavenging activity (74.2%) compared to fruit extract (60.4%). Moreover, both fruit extract and the synthesized AgNPs showed the cytotoxicity towards Rat L6 skeletal muscle cell line at different concentrations, but the highest inhibition percentage was recorded for AgNPs at concentration of 100 μg/ml.